Psychosocial Problems of Families Living with an Addicted Family Member - H Mancheri; ND Sharifi Neyestanak; N Seyedfatemi; M Heydari; M Ghodoosi (Iran University of Medical Sciences, 2013)
Abstract   Background & Aim: Addiction (Substance addicted) as one of the health problems in the present century can influence physical, emotional and social aspects of addicted people and impose psychosocial problems for their families and society. Accordingly, this study aimed to examine social, psychosocial problems in families with an addicted member.   Material & Methods: It was a descriptive, correlational study. The sample consisted of 400 close family members of the addicted people who were randomly recruited. Data was collected by SCL-90 questionnaire analyzed by SPSS-PC (v.16).   Result: The findings showed that most subjects suffered moderate depression (36.8%) and moderate anxiety (36 . 4%). Also 36% of them had low levels of aggression and 35.8% had moderate interpersonal sensitivity.   Conclusion: Based on the findings , it can be concluded that addicted members of families can affect the mental health of other family members . Proposing educational programs by nurses for high risk persons would prevent addiction-induced difficulties by knowledge promotion and behavior change.   Received: 30 May 2013   Accepted: 3 Sep 2013